Helical Distortion in Tryptophan- and Lysine-Anchored Membrane-Spanning α-Helices as a Function of Hydrophobic Mismatch: A Solid-State Deuterium NMR Investigation Using the Geometric Analysis of Labeled Alanines Method - Daily, Anna E. (The Biophysical Society, 2008)
We used solid-state deuterium NMR spectroscopy and geometric analysis of labeled alanines to investigate the structure and orientation of a designed synthetic hydrophobic, membrane-spanning α-helical peptide that is anchored within phosphatidylcholine (PC) bilayers using both Trp and Lys side chains near the membrane/water interface. The 23-amino-acid peptide consists of an alternating Leu/Ala core sequence that is expected to be α-helical, flanked by aromatic and then cationic anchors at both ends of the peptide: acetyl-GKALW(LA)(6)LWLAKA-amide (KWALP23). The geometric analysis of labeled alanines method was elaborated to permit the incorporation and assignment of multiple alanine labels within a single synthetic peptide. Peptides were incorporated into oriented bilayers of dilauroyl- (di-C12:0-), dimyristoyl- (di-C14:0-), or dioleoyl- (di-C18:1c-) PC. In the C12:0 and C14:0 lipids, the (2)H-NMR quadrupolar splittings for the set of six core alanines could not be fit to a canonical undistorted α-helix. Rather, we found that a model containing a helical distortion, such as a localized discontinuity or “kink” near the peptide and bilayer center, could fit the data for KWALP23 in these shorter lipids. The suggestion of helix distortion was confirmed by (2)H-NMR spectra for KWALP23 in which Leu(8) was changed to deuterated Ala(8). Further analysis involving reexamination of earlier data led to a similar conclusion that acetyl-GWW(LA)(8)LWWA-amide (WALP23) is distorted in dilauroyl-PC, allowing significant improvement in the fitting of the (2)H-NMR results. In contrast, WALP23 and KWALP23 are well represented as undistorted α-helices in dioleoyl-PC, suggesting that the distortion could be a response to hydrophobic mismatch between peptide and lipids.